Enhancing programmed cell death protein 1 axis inhibition in head and neck squamous cell carcinoma: Combination immunotherapy. (June 2021) - Vathiotis, Ioannis A.; Johnson, Jennifer M.; Argiris, Athanassios
Highlights: Response to PD-1/L1 axis inhibitors is limited to few patients with R/M HNSCC. Combination immunotherapy is used to enhance the efficacy of PD-1/L1 inhibitors. New targets are in the spotlight of preclinical and clinical research. Abstract: Anti-programmed cell death protein 1 immunotherapy has become the new standard in the treatment of patients with recurrent or metastatic head and neck squamous cell carcinoma (HNSCC). However, the population that benefits is small, warranting drug combinations and novel approaches. HNSCC is a profoundly immunosuppressive disease, characterized by the interplay among different immune regulatory pathways. As clinical trials evaluating immunotherapy combinations in patients with HNSCC have started producing preliminary results, preclinical evidence on potential new targets for combination immunotherapy continues to accumulate. This review summarizes emerging clinical and preclinical data on immunotherapy combinations for the treatment of HNSCC.